PENERAPAN MODEL PBL BERBASIS MEDIA BENTANG ALAM (BENAM) UNTUK TINGKATKAN HASIL BELAJAR IPAS KELAS V SDN 01 PUNTEN BATU - Maulita Rini Prawesti; Arina Restian; Nur Suhartanti (ADISAM PUBLISHER, 2026)
This study aims to improve the learning outcomes of IPAS (Natural and Social Sciences) for fifth-grade students through the application of the Problem Based Learning (PBL) model based on Natural Landscape (BENAM) media. The research was conducted at SDN Punten 01 Batu using the Classroom Action Research (CAR) method with two cycles. The research subjects were 23 students from class VA. The results showed a significant improvement from cycle I to cycle II. At the end of cycle I, the class average score reached 44% with 12 students completing and 11 students not completing. Cycle II showed an improvement with the class average score reaching 74%, where 21 students completed and only 2 students did not complete. This 27% increase indicates the effectiveness of the PBL model assisted by BENAM media in improving IPAS learning outcomes. Additionally, students reported increased motivation and enjoyment in the learning process. In conclusion, the application of the PBL model based on BENAM media proved effective in improving IPAS learning outcomes and creating a more meaningful learning experience for fifth-grade elementary school students.